(untitled) (Research, Society and Development, 2022)
The Technologist in Radiology is a professional who integrates the multiprofessional team in the health area, and works with the application of ionizing radiation in radiodiagnosis and therapy. In the radiotherapy sector, this professional can act as a radiology technologist or dosimetrist. The main objective of this article is to analyze the curriculum of the academic training of radiology technologists for professional performance as dosimetrists. This is a qualitative-quantitative research with a documentary analysis approach. The political-pedagogical projects of six Brazilian federal public institutions that offer graduate courses in technology in radiology were listed. From these documents the program contents were correlated with the American Association of Medical Dosimetrists (AAMD) Curriculum Guideline for Dosimetrist Training. The current Brazilian regulations do not contemplate the role of the dosimetrist in the radiation therapy sector. The technologist in radiology contemplates in his/her education the prerequisites suggested by the AAMD for entering a residency course in dosimetry; however, in Brazil, the professional is unable to enter residency programs. The non-uniformity of the programmatic content among the disciplines was identified. Of the six institutions studied, one of them does not include radiotherapy in its political-pedagogical project, which hinders a single and specific training that ensures the unified offer of this training.